Integrating Logistics Management in a Circular Economy - Pisitkasem, Phat (Rajapark Journal, 2022)
Environmental issues are currently a major concern throughout the world, including Thailand. Partly due to the indiscriminate use of natural resources without thorough consideration of the entire system, resulting in resource scarcity, waste problems, and other environmental issues. The Circular Economy concept entails planning ahead of time for the efficient use of resources throughout the system in order to ensure product production. The usage of those items and the reintroduction of those utilized products into the system by adding value to the system reduces the consumption of new resources and the subsequent development of waste or rubbish. Integrating logistics management is a technique or method that can assist save costs and improve operational efficiency. This article discusses approaches or systems for supporting operations, such as the just in time system, economics order quantity, material requirement planning, and lean, which, if implemented, will allow the business to manage resources in a cost-effective manner. This will result in a response to the aims of society as a whole in terms of shared responsibility for solving problems, eliminating problems, and improving the environment in order to return to a state that will allow people in our society and our children in the future to live happily.